2020
DOI: 10.1111/aji.13321
|View full text |Cite
|
Sign up to set email alerts
|

Does thyroid autoimmunity affect the reproductive outcome in women with thyroid autoimmunity undergoing assisted reproductive technology?

Abstract: Problem: Our study aims to investigate whether the anti-thyroperoxidase antibody (TPO-Ab) and TSH level in euthyroid women have any association with reproductive outcomes after the ART cycle. Methods of study: A total of 1107 patients who were enrolled in the study were divided into four groups based on serum TSH level and TPO-Ab status: group A,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Some studies have reported no discernible association between the presence of TPO-Ab and rates of miscarriage or successful deliveries ( 29 , 30 ). In contrast, others reported higher rates of miscarriage and lower delivery rates in TPO-Ab-positive patients compared to negative patients due to shifts in metabolic and immune status ( 31 33 ). Vitamin D deficiency is considered a trigger for autoimmune diseases and is decreased in patients with autoimmune thyroid diseases.…”
Section: Discussionmentioning
confidence: 91%
“…Some studies have reported no discernible association between the presence of TPO-Ab and rates of miscarriage or successful deliveries ( 29 , 30 ). In contrast, others reported higher rates of miscarriage and lower delivery rates in TPO-Ab-positive patients compared to negative patients due to shifts in metabolic and immune status ( 31 33 ). Vitamin D deficiency is considered a trigger for autoimmune diseases and is decreased in patients with autoimmune thyroid diseases.…”
Section: Discussionmentioning
confidence: 91%
“…Some studies found that the presence of TPO‐Ab was not associated with pregnancy loss or delivery rate (DR) (Litwicka et al, 2015; Plowden et al, 2016; Unuane et al, 2017). By contrast, others reported that TPO‐Ab positive patients showed higher miscarriage rat (MR) and lower DR than negative patients (Seungdamrong et al., 2017; He et al, 2020; Zhong et al, 2012). A previous meta‐analysis involving 14 literatures showed that TAI had no significant adverse effect on the ART outcomes, including clinical pregnancy rate, biochemical pregnancy rate, MR, DR and the number of oocytes retrieved (Venables et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…T A B L E 1 Summary of characteristics of the included studies. He et al, 2020;Kutteh et al, 1999;Muller et al, 1999); TG-Ab included as indicator of TAI in 6 articles (Karacan et al, 2013;Kilic et al, 2008;Liu et al, 2020;Mintziori et al, 2014;Sakar et al, 2016;Tan et al, 2014). Finally, 7 papers published from 2003 to 2020, were included for our meta-analysis (Figure 1) (Chen et al, 2017;Łukaszuk et al, 2015;Negro et al, 2005Negro et al, , 2007Poppe et al, 2003;Unuane et al, 2016Unuane et al, , 2017.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations